A cross-case analysis of rural robotics teacher leaders’ identity development - Meador, Audrey; Raygoza, Alyssa; Irvin, Matt; Starrett, Angie; Quiroz, Beatrice; Cartiff, Brian (Frontiers in Education, 2025)
As educational robotics (ER) becomes an increasingly popular extracurricular opportunity for K-12 STEM learning, researchers continue to explore effective learning environments and teaching approaches for this integrated form of instruction. However, limited research has examined the experiences of rural educators implementing robotics programs or how these programs contribute to rural teacher leadership development. This qualitative study examines the experiences of rural robotics teachers (RRTs) and the development of their identities as rural STEM teacher leaders. Guided by the rural teacher leadership in the science and mathematics framework, the findings highlight leadership skills that helped RRTs pioneer ER programs in rural schools. The results offer insights into how rural schools can support teacher leadership development in STEM, particularly through integrated, innovative STEM learning approaches. Implications from this study strengthen the support for the rural teacher leadership framework in other STEM content areas.